2018
DOI: 10.1002/ecs2.2117
|View full text |Cite
|
Sign up to set email alerts
|

What drives biological nitrogen fixation in high arctic tundra: Moisture or temperature?

Abstract: Biological nitrogen (N2) fixation is one of the main sources of available N for pristine ecosystems such as subarctic and arctic tundra. Although this has been acknowledged more than a decade ago, few attempts have been undertaken to identify the foremost driver of N2 fixation in the high Arctic. Here, we report results from in situ measurements of N2 fixation throughout the main growing period (June–August) in high arctic tundra, Greenland, in climate change treatments, shading and warming, and control. Nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 52 publications
5
49
0
Order By: Relevance
“…On the contrary, we found a net positive effect of warming on soil DON. Although there are exceptions to this trend (e.g., Rousk et al 2018, Stark et al 2018, our meta-analysis suggests that warming in cold ecosystems could lead to a net accumulation of belowground N in the form of DON. Similar increases in DON with warming have been observed elsewhere (e.g., Kane et al 2014, Schaeffer et al 2013.…”
Section: Warming Leads To a Net Accumulation Of Don In Cold Ecosystemsmentioning
confidence: 58%
See 1 more Smart Citation
“…On the contrary, we found a net positive effect of warming on soil DON. Although there are exceptions to this trend (e.g., Rousk et al 2018, Stark et al 2018, our meta-analysis suggests that warming in cold ecosystems could lead to a net accumulation of belowground N in the form of DON. Similar increases in DON with warming have been observed elsewhere (e.g., Kane et al 2014, Schaeffer et al 2013.…”
Section: Warming Leads To a Net Accumulation Of Don In Cold Ecosystemsmentioning
confidence: 58%
“…For example, in a subarctic wet heath in northern Sweden, overall growing-season N fixation by moss-associated diazotrophs was about three times larger in plots that had been warmed with dome-shaped plastic greenhouses for 10 yr than in unmanipulated plots (Sorensen and Michelsen 2011). A more recent study at the same site , and a similar experiment in the high Arctic, Greenland (Rousk et al 2018), found no effects of warming on N fixation. In the same area, 21 yr of warming had either no effect or a negative effect on N fixation in the mosses Hylocomium splendens and Aulacomnium turgidum, respectively (Sorensen et al 2012).…”
Section: No Evidence Of Warming Affecting N Fixation In a Consistent mentioning
confidence: 90%
“…N 2 fixation rates of moss-associated diazotrophic bacteria can be expected to increase with temperature, as metabolic processes in microorganisms increase with temperature and the enzyme nitrogenase is more active at higher temperatures [30]. Temperature induced drought however, can inhibit N 2 fixation rates, especially cyanobacterial N 2 fixation [9, 24, 3136]. Temperature effects on N 2 fixation rates might also be influenced by physiological adaptation of diazotrophic communities, or shifts to a species composition better suited to the new conditions [31, 37, 38].…”
Section: Introductionmentioning
confidence: 99%
“…Temperature induced drought however, can inhibit N 2 fixation rates, especially cyanobacterial N 2 fixation [9, 24, 3136]. Temperature effects on N 2 fixation rates might also be influenced by physiological adaptation of diazotrophic communities, or shifts to a species composition better suited to the new conditions [31, 37, 38]. Despite the importance of microbial communities for plant functioning and ecosystem processes, the effect of warming on moss microbial communities has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…In Arctic ecosystems, N2 fixation is known as the major N input into ecosystems (Granhall and Selander, 1973;Rousk et al, 2017Rousk et al, , 2018 with N fixation rates between 1 and 29 kg N ha -1 a -1 , depending on which N2 fixing species (e.g. free-living or moss-associated cyanobacteria) is dominating (Rousk et al, 2017).…”
Section: Molecular and Isotopic Analyses Confirm The Differences In Tmentioning
confidence: 99%